Preparation method of nanoscale powder, nanoscale powder and all-solid-state battery
By mixing the sulfide solid electrolyte raw powder and non-polar solvent with a dispersant containing silicone structural units, powderification and drying, the problem of easy sedimentation of sulfide solid electrolyte in non-polar solvents is solved, and efficient preparation of nano-scale powders and the performance improvement of all-solid-state batteries are achieved.
Patent Information
- Application Number
- CN202411609580.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-18
AI Technical Summary
The sulfide solid electrolyte is unstable in polar organic solvents and easily settles in non-polar solvents, making it difficult to prepare its nano-scale powder.
A dispersant containing silicone structural units is mixed with the sulfide solid electrolyte raw powder and a non-polar solvent, powdered by a ball mill, and dried to prepare nano-scale powder.
The problem of sulfide solid electrolyte easily settled in non-polar solvents is effectively avoided, the difficulty of preparing nano-scale powders is reduced, and the first discharge capacity of the positive electrode of the all-solid state battery is improved.
Smart Images

Figure CN119650823A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of all-solid-state batteries, and in particular to a method for preparing nano-scale powder, nano-scale powder and an all-solid-state battery. Background Art
[0002] As the core component of solid-state batteries, solid electrolytes need to be refined and crushed before being applied to pole pieces or electrolyte films to ensure good contact between particles, which is conducive to the transmission of lithium ions. Therefore, it is necessary to ensure the uniformity of solid electrolyte particles. In the preparation method of sulfide solid electrolyte nanopowder, sulfide solid electrolytes are unstable in polar organic solvents, while sulfide solid electrolytes are easy to settle in non-polar solvents, and their nanopowders are difficult to prepare. Summary of the invention
[0003] In view of the above problems, the object of the present invention is to provide a simple method for preparing nanoscale powder, nanoscale powder and all-solid-state battery, and the technical solution is as follows:
[0004] In one aspect, a method for preparing a nanoscale powder is provided, the method comprising:
[0005] Providing a first mixture; the first mixture comprises: sulfide solid electrolyte raw powder, a non-polar solvent and a dispersant; the dispersant comprises a siloxane structural unit;
[0006] Powdering the first mixture to obtain a second mixture;
[0007] The second mixture is dried to obtain the nanoscale powder.
[0008] In an exemplary embodiment, the sulfide solid electrolyte raw powder includes (100-xy)Li2S·xP2S5·yM m N n ;
[0009] Among them, 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is one or more of Li, Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I.
[0010] In an exemplary embodiment, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 1% to 70%.
[0011] In an exemplary embodiment, the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder is 0.05% to 5%.
[0012] In an exemplary embodiment, the dispersant includes: one or a combination of polydimethylsiloxane, phenyltrimethylpolysiloxane, polymethylhydrogensiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetrakis-trimethylsiloxysilane, alkyl-modified silicone and amino-modified silicone.
[0013] In an exemplary embodiment, the non-polar solvent includes one or a combination of cyclohexane, hexane, pentane, toluene, dichlorotoluene, petroleum ether, ethyl ether, ethyl acetate, methyl acetate, heptane, chloroform, and dibutyl ether.
[0014] In an exemplary embodiment, the powdering of the first mixture to obtain the second mixture comprises:
[0015] Powdering the first mixture by ball milling to obtain the second mixture;
[0016] The ball-to-material mass ratio of the ball mill is (5-10):1;
[0017] The ball milling time is 1 to 5 hours.
[0018] In an exemplary embodiment, the drying time is 4 to 8 hours; the drying temperature is 60 to 120°C.
[0019] On the other hand, the present invention further provides a nano-scale powder, including a nano-scale powder prepared by any of the preparation methods described above.
[0020] On the other hand, the present invention also provides an all-solid-state battery, comprising the nanoscale powder described above.
[0021] The present invention discloses a method for preparing nano-scale powder, which comprises: providing a first mixture; the first mixture comprises: sulfide solid electrolyte raw powder, a non-polar solvent and a dispersant; the dispersant comprises a siloxane structural unit; the first mixture is subjected to a powdering treatment to obtain a second mixture; the second mixture is dried to obtain a nano-scale powder. By using a dispersant comprising a siloxane structural unit, the anchoring group and Si-S bonding force in the dispersant are utilized to adsorb on the surface of the sulfide solid electrolyte raw powder, and the spatial hindrance of the solvated chain end of the dispersant is combined to avoid the problem that the sulfide solid electrolyte raw powder is easy to settle in the non-polar solvent, thereby reducing the difficulty of preparing the nano-scale powder, thereby obtaining the nano-scale powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 is a flow chart of a method for preparing nano-scale powder provided by an embodiment of the present invention;
[0024] Figure 2 is a structural formula of a siloxane structural unit provided in an embodiment of the present invention;
[0025] Figure 3 This is a SEM comparison diagram of LPSC powder obtained by using a dispersant and without using a dispersant provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] As an important carrier of energy conversion and storage, secondary batteries have higher requirements with the global industrialization and widespread application of computers - higher energy density, longer cycle life and higher safety. All-solid-state batteries use non-flammable, high temperature resistant, non-corrosive, non-volatile solid electrolytes as lithium ion transmission channels, solving the problems of electrolyte leakage and thermal runaway in traditional lithium-ion batteries, avoiding safety hazards, and have ultra-high potential energy density. It is one of the important development directions of the next generation of secondary batteries.
[0028] As the core component of solid-state batteries, solid electrolytes need to be refined and crushed before being applied to pole pieces or electrolyte films to ensure good contact between particles, which is conducive to the transmission of lithium ions. Most sulfide solid electrolyte nanopowders use spray drying technology, but the equipment consumes a lot of energy and overheating causes the powder performance to decrease. In order to ensure the uniformity and output of particles, wet grinding becomes the best choice. However, sulfide solid electrolytes are unstable in polar organic solvents and easily settle in non-polar solvents, and their nanopowders are difficult to prepare.
[0029] Therefore, it is very necessary to develop a simple method for preparing nanoscale powders to prepare sulfide solid electrolyte nanoscale powders.
[0030] The present invention provides a method for preparing nano-scale powder. Figure 1 , Figure 1 The present invention is a flow chart of a method for preparing nano-scale powder, which comprises the following steps:
[0031] Step S1: providing a first mixture; the first mixture comprises: sulfide solid electrolyte raw powder, a non-polar solvent and a dispersant; the dispersant comprises a siloxane structural unit.
[0032] Specifically, the sulfide solid electrolyte raw powder refers to a sulfide solid electrolyte that has not been subjected to a powdering treatment. By using a dispersant containing a siloxane structural unit, for example, a structural formula of a siloxane structural unit can be found in Figure 2 ,like Figure 2 The polymer shown contains Si-O bonds to form the main chain structure, wherein a represents the number of siloxane bonds of the anchoring group, b represents the number of siloxane monomers, a≥1, b≥1; the anchoring group and Si-S bonding force in the dispersant are utilized to adsorb on the surface of the sulfide solid electrolyte raw powder, and the spatial hindrance of the solvated chain end of the dispersant is combined to avoid the problem of easy sedimentation of the sulfide solid electrolyte raw powder in non-polar solvents, thereby reducing the difficulty of preparing its nano-scale powder.
[0033] Step S2: Powdering the first mixture to obtain a second mixture.
[0034] Specifically, the sulfide solid electrolyte raw powder is subjected to a powdering process to obtain the sulfide solid electrolyte powder with nano-scale particle size.
[0035] Step S3: drying the second mixture to obtain nanometer-scale powder.
[0036] Specifically, the purpose of removing the dispersant and the non-polar solvent is achieved by drying the second mixture.
[0037] In the embodiment of the present application, the sulfide solid electrolyte raw powder includes (100-xy)Li2S·xP2S5·yM m N n ;
[0038] Among them, 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is one or more of Li, Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I.
[0039] For example, by using the (100-xy)Li2S·xP2S5·yM m N nThe raw powder of the sulfide solid electrolyte in the embodiment of the present application is used to prepare the nano-scale powder of the sulfide solid electrolyte.
[0040] In the embodiment of the present application, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 1% to 70%.
[0041] Specifically, a better preparation effect is obtained by feeding the sulfide solid electrolyte raw powder in a ratio of 1% to 70% of the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent, wherein preferably, 20% to 50% is used.
[0042] In the embodiment of the present application, the mass ratio of the dispersant to the mass ratio of the sulfide solid electrolyte raw powder is 0.05% to 5%.
[0043] Specifically, the embodiments of the present application take into account that adding too much dispersant will affect the ionic conductivity of the prepared nano-scale powder. Therefore, by controlling the amount of dispersant added within the range of 0.05% to 5% of the mass of the dispersant relative to the mass of the sulfide solid electrolyte raw powder, the ionic conductivity of the nano-scale powder is not affected, while the preparation effect is improved, wherein 0.1% to 0.5% is preferred.
[0044] In an embodiment of the present application, the dispersant includes: polydimethylsiloxane, phenyltrimethylpolysiloxane, polymethylhydrogensiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetrakis-trimethylsiloxysilane, alkyl-modified silicone and amino-modified silicone, or a combination of several thereof.
[0045] Specifically, a dispersant containing a siloxane structural unit is introduced by using one or a combination of polydimethylsiloxane (PDMS), phenyltrimethylpolysiloxane (PTTMS), polymethylhydrogensiloxane (PMHS), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), tetramethyltetrahydrocyclotetrasiloxane (D4H), tetrakis-trimethylsiloxysilane (TTMS), alkyl-modified silicone, and amino-modified silicone as a dispersant, and the dispersant is adsorbed on the surface of the sulfide solid electrolyte raw powder through the anchoring group and Si-S bonding force in the dispersant. In combination with the spatial hindrance of the solvated chain end of the dispersant, the problem of easy sedimentation of the sulfide solid electrolyte raw powder in a non-polar solvent is avoided, thereby reducing the difficulty of preparing the nano-scale powder thereof.
[0046] In the embodiments of the present application, the non-polar solvent includes one or a combination of cyclohexane, hexane, pentane, toluene, dichlorotoluene, petroleum ether, ethyl ether, ethyl acetate, methyl acetate, heptane, chloroform, and dibutyl ether.
[0047] Specifically, by using the above-mentioned non-polar solvent as the non-polar solvent of the embodiment of the present application and wet grinding, the uniformity of the particles is ensured and the yield is improved.
[0048] In the embodiment of the present application, the first mixture is powdered to obtain a second mixture comprising:
[0049] Powdering the first mixture by ball milling to obtain a second mixture;
[0050] The ball-to-material mass ratio of ball milling is (5-10):1;
[0051] The ball milling time is 1 to 5 hours.
[0052] Specifically, the effect of the ball milling on the powdering of the first mixture is improved by ball milling and by adjusting the ball milling time and the ball-to-material mass ratio of the ball milling.
[0053] In the embodiments of the present application, the drying time is 4 to 8 hours; the drying temperature is 60 to 120°C.
[0054] Specifically, by controlling the drying time and the drying temperature, the dispersant and the non-polar solvent are removed to obtain the nanometer-scale powder.
[0055] The embodiments of the present application also provide a nano-scale powder, including the nano-scale powder prepared by any of the methods disclosed in the embodiments of the present application.
[0056] Specifically, a nanoscale powder provided in an embodiment of the present application includes a method disclosed in an embodiment of the present application by providing a first mixture, wherein the first mixture includes: a sulfide solid electrolyte raw powder, a non-polar solvent and a dispersant, wherein the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 1% to 70%, and the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder is 0.05% to 5%; the sulfide solid electrolyte raw powder includes (100-xy)Li2S·xP2S5·yM m N n, wherein 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is one or more of Li, Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I; the dispersant comprises a siloxane structural unit, and the dispersant comprises: one or a combination of polydimethylsiloxane, phenyltrimethylpolysiloxane, polymethylhydrogensiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetra-trimethylsiloxysilane, alkyl-modified silicone and amino-modified silicone; the non The polar solvent includes one or a combination of cyclohexane, hexane, pentane, toluene, dichlorotoluene, petroleum ether, ether, ethyl acetate, methyl acetate, heptane, chloroform, and dibutyl ether; the first mixture is then powdered to obtain a second mixture, wherein the first mixture can be powdered by ball milling to obtain the second mixture, wherein the ball-to-material mass ratio of the ball milling is (5-10):1, and the ball milling time is 1-5 hours; finally, the second mixture is dried, wherein the drying time is 4-8 hours, and the drying temperature is 60-120° C., thereby obtaining a nano-scale powder.
[0057] The embodiments of the present application also provide an all-solid-state battery, comprising any one of the nanoscale powders disclosed in the embodiments of the present application.
[0058] Specifically, the all-solid-state battery of the embodiments of the present application includes any one of the nanoscale powders disclosed in the embodiments of the present application.
[0059] The present invention has no special requirements for the preparation of the battery, and the conventional preparation method of the all-solid-state battery in the art can be adopted. The specific preparation process is well known in the field of solid-state batteries and will not be described in detail here.
[0060] The technical solution of the present application is described below in conjunction with specific embodiments.
[0061] The nanoscale powders obtained in the following examples and the powders prepared in the following comparative examples were subjected to relevant tests and characterizations.
[0062] Ionic conductivity test: The obtained nano-scale powder or powder was cold pressed into sheets at room temperature 25°C, and an AC impedance test was performed using a stainless steel sheet as a blocking electrode.
[0063] Particle size test: The nano-scale powder or powder median particle size D50 obtained by laser particle size analyzer test.
[0064] Morphology characterization: The actual morphology of the obtained solid electrolyte powder was characterized by scanning electron microscopy (SEM).
[0065] Electrochemical performance test: The obtained nano-scale powder or powder is applied to the positive electrode sheet. The positive electrode active material is nickel cobalt manganese oxide (NCM811) with a median particle size D50 of 5μm; the positive electrode active material, solid electrolyte, conductive agent (Super P), and binder (PVDF) are mixed in a mass ratio of 80:15:3:2, and the positive electrode sheet is prepared by wet coating and drying. The positive electrode sheet is assembled with metal lithium into a principle half-cell for metal lithium, and the first discharge specific capacity of the positive electrode at a rate of 0.1C is tested.
[0066] In specific implementation, the present invention does not specifically limit the total mass of the first mixture. Generally, the volume of the first mixture accounts for about 20% of the volume of the ball mill.
[0067] Example 1
[0068] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0069] A first mixture is obtained by mixing argyrodite-type sulfide solid electrolyte raw powder LPSC with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent being 20%, and then adding 0.1% of PDMS g of the dispersant to the mass of the sulfide solid electrolyte raw powder. The mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1, and the mixture is ball milled for 3 hours to obtain a second mixture. The second mixture is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0070] Comparative Example 1, compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder. Figure 3 .
[0071] Example 2
[0072] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0073] The sulfide solid electrolyte raw powder LPSC is mixed with hexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 35%, and then the mass ratio of the dispersant PTTMS to the mass of the sulfide solid electrolyte raw powder is 0.3% to obtain a first mixture, which is powdered by ball milling with a ball-to-material ratio of 10:1 and a ball mass of 1.5 g. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 85°C for 8 hours to obtain nano-scale LPSC powder.
[0074] Comparative Example 2: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0075] Example 3
[0076] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0077] The tetragonal sulfide solid electrolyte powder LGPS was mixed with pentane, the mass ratio of the sulfide solid electrolyte powder to the total mass of the sulfide solid electrolyte powder and the non-polar solvent was 30%, and then the mass ratio of the dispersant PMHS to the mass of the sulfide solid electrolyte powder was 0.2% to obtain a first mixture, which was powdered by ball milling with a ball-to-material mass ratio of 10:1 and a ball mass of 1.5. After ball milling for 3 hours, a second mixture was obtained, which was placed in an oven and dried at 90°C for 8 hours to obtain nano-scale LGPS powder.
[0078] Comparative Example 3: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LGPS powder.
[0079] Example 4
[0080] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0081] Iodine-doped Thio-LISICONⅡ sulfide solid electrolyte raw powder 728I and toluene, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 45%, and then the mass ratio of the dispersant D4 to the mass of the sulfide solid electrolyte raw powder is 0.5% to obtain a first mixture, which is powdered by ball milling with a ball-to-material mass ratio of 5:1 and a ball mass of 5. After ball milling for 1 hour, a second mixture is obtained, which is placed in an oven and dried at 60°C for 8 hours to obtain nano-scale 728I powder.
[0082] Comparative Example 4: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain 728I powder.
[0083] Example 5
[0084] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0085] The sulfide solid electrolyte raw powder LPSC is mixed with dichlorotoluene, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 50%, and then the mass ratio of the dispersant D5 to the mass of the sulfide solid electrolyte raw powder is 0.3% to obtain a first mixture, which is powdered by ball milling with a ball-to-material mass ratio of 5:1 and a ball mass of 5. After ball milling for 5 hours, a second mixture is obtained, which is placed in an oven and dried at 120°C for 4 hours to obtain nano-scale LPSC powder.
[0086] Comparative Example 5: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0087] Example 6
[0088] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0089] The sulfide solid electrolyte raw powder LPSC is mixed with dibutyl ether, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 30%, and then D4H with the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder being 0.3% is added to obtain a first mixture, which is powdered by ball milling with a ball-to-material mass ratio of 10:1 and a ball mass of 0.5. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 100°C for 8 hours to obtain nano-scale LPSC powder.
[0090] Comparative Example 6: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0091] Example 7
[0092] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0093] The sulfide solid electrolyte raw powder LPSC is mixed with petroleum ether, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 35%, and then the mass ratio of the dispersant TTMS to the mass of the sulfide solid electrolyte raw powder is 0.3% to obtain a first mixture, which is powdered by ball milling with a ball-to-material mass ratio of 10:1 and a ball mass of 20. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 90°C for 8 hours to obtain nano-scale LPSC powder.
[0094] Comparative Example 7: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0095] Example 8
[0096] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0097] The sulfide solid electrolyte raw powder LPSC is mixed with ethyl acetate, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 25%, and then 0.3% of alkyl-modified silicone is added as a dispersant to the mass of the sulfide solid electrolyte raw powder to obtain a first mixture, which is powdered by ball milling with a ball-to-material mass ratio of 10:1 and a ball mass of 0.5. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 100°C for 6 hours to obtain nano-scale LPSC powder.
[0098] Comparative Example 8: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0099] Example 9
[0100] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0101] The sulfide solid electrolyte raw powder LPSC is mixed with heptane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 30%, and then the amino-modified silicone with the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder being 0.3% is added to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material ratio of 10:1 and a ball mass of 1.5. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 90°C for 8 hours to obtain nano-scale LPSC powder.
[0102] Comparative Example 9: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0103] Example 10
[0104] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0105] The sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 20%, and then the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder is 0.1% of PDMS and D4H mixed dispersant (mass ratio is 3:2) to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1 and a ball mass of 1.5. After ball milling for 3 hours, a second mixture is obtained, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0106] Embodiment 11
[0107] This embodiment is used to illustrate the preparation method of the nanometer-grade powder and the nanometer-grade powder of the present invention.
[0108] The sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 1%, and then the mass ratio of the dispersant PDMS to the mass of the sulfide solid electrolyte raw powder is 0.1% to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1. The mixture is ball milled for 3 hours to obtain a second mixture, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0109] Comparative Example 11, compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0110] Example 12
[0111] The sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 70%, and then PDMS is added in the mass ratio of the dispersant to the mass of the sulfide solid electrolyte raw powder is 0.1% to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1. The mixture is ball milled for 3 hours to obtain a second mixture, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0112] Comparative Example 12: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0113] Embodiment 13
[0114] The sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 20%, and then the mass ratio of the dispersant PDMS to the mass of the sulfide solid electrolyte raw powder is 0.05% to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1. The mixture is ball milled for 3 hours to obtain a second mixture, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0115] Embodiment 14
[0116] The sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 20%, and then the mass ratio of the dispersant PDMS to the mass ratio of the sulfide solid electrolyte raw powder is 5% to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1. The mixture is ball milled for 3 hours to obtain a second mixture, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0117] Embodiment 15
[0118] Sulfide solid electrolyte raw powder LPSC is mixed with cyclohexane and toluene, the mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 20%, wherein the ratio of cyclohexane to toluene is 1:1, and then PDMS is added in a mass ratio of 0.1% to the mass of the sulfide solid electrolyte raw powder to obtain a first mixture, and the mixture is powdered by ball milling with a ball-to-material mass ratio of 10:1. The mixture is ball milled for 3 hours to obtain a second mixture, which is placed in an oven and dried at 60°C for 6 hours to obtain nano-scale LPSC powder.
[0119] Comparative Example 15: Compared with the example, no dispersant was added, and other conditions remained unchanged to obtain LPSC powder.
[0120] Table 1. Test results of the powders prepared in the examples and comparative examples
[0121]
[0122]
[0123] As can be seen from Table 1, by comparing Example 1 with Comparative Example 1, it can be seen that without adding a dispersant, the sulfide sulfide solid electrolyte raw powder is easy to settle in a non-polar solvent, and the effect of particle size refinement cannot be achieved, and the original particle size is basically maintained. Combined with the electrochemical performance data, it can be seen that the use of a dispersant achieves a stable dispersion of the solid electrolyte in a non-polar solvent medium, achieving the purpose of particle size refinement. The sulfide solid electrolyte nanopowder is fully mixed with the positive electrode particles, ensuring good contact between the positive electrode particles, which is conducive to capacity development.
[0124] By comparing Example 1 with Example 10, it can be seen that the mixed dispersant is not as effective as a single dispersant, and the ionic conductivity after refinement is not as good as a single PDMS dispersant, which leads to a lower positive electrode capacity. PDMS dispersant is preferred.
[0125] It can be seen from the above technical scheme of the embodiment of the present invention that the present invention discloses a method for preparing nano-scale powder, which comprises: providing a first mixture; the first mixture comprises: sulfide solid electrolyte raw powder, non-polar solvent and dispersant; the dispersant comprises siloxane structural units; the first mixture is powderized to obtain a second mixture; the second mixture is dried to obtain nano-scale powder. By using a dispersant comprising a siloxane structural unit, the anchoring group and Si-S bonding force in the dispersant are utilized to adsorb on the surface of the sulfide solid electrolyte raw powder, and the spatial hindrance of the solvated chain end of the dispersant is combined to avoid the problem of easy sedimentation of the sulfide solid electrolyte raw powder in the non-polar solvent, thereby reducing the difficulty of preparing the nano-scale powder and improving the positive first discharge capacity of the all-solid-state battery based on the nano-scale powder.
[0126] The above description has fully disclosed the specific embodiments of the present invention. It should be pointed out that any changes made by those skilled in the art to the specific embodiments of the present invention do not deviate from the scope of the claims of the present invention. Accordingly, the scope of the claims of the present invention is not limited to the above specific embodiments.
Claims
1. A method for preparing nano-scale powder, characterized in that: The method comprises: Providing a first mixture; the first mixture comprises: sulfide solid electrolyte raw powder, a non-polar solvent and a dispersant; the dispersant comprises a siloxane structural unit; Powdering the first mixture to obtain a second mixture; The second mixture is dried to obtain the nanoscale powder.
2. The method according to claim 1, characterized in that: The sulfide solid electrolyte raw powder includes (100-xy)Li2S·xP2S5·yM m N n ; Among them, 0≤x<100, 0≤y<100, 0≤x+y<100, 0≤m<4, 0≤n<6, M is one or more of Li, Ge, Si, Sn, Sb, and N is one or more of Se, O, Cl, Br, and I.
3. The method according to claim 1, characterized in that The mass ratio of the sulfide solid electrolyte raw powder to the total mass of the sulfide solid electrolyte raw powder and the non-polar solvent is 1% to 70%.
4. The method according to claim 1, characterized in that: The mass ratio of the dispersant to the mass ratio of the sulfide solid electrolyte raw powder is 0.05% to 5%.
5. The method according to claim 1, characterized in that: The dispersant includes: one or a combination of polydimethylsiloxane, phenyltrimethylpolysiloxane, polymethylhydrogensiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, tetramethyltetrahydrocyclotetrasiloxane, tetrakis-trimethylsiloxysilane, alkyl-modified silicone and amino-modified silicone.
6. The method according to claim 1, characterized in that The non-polar solvent includes one or a combination of cyclohexane, hexane, pentane, toluene, dichlorotoluene, petroleum ether, ethyl ether, ethyl acetate, methyl acetate, heptane, chloroform, and dibutyl ether.
7. The method according to claim 1, characterized in that The powdering of the first mixture to obtain the second mixture comprises: Powdering the first mixture by ball milling to obtain the second mixture; The ball-to-material mass ratio of the ball mill is (5-10):1; The ball milling time is 1 to 5 hours.
8. The method according to claim 1, characterized in that The drying time is 4 to 8 hours; the drying temperature is 60 to 120°C.
9. A nanometer-scale powder, characterized in that: The invention relates to a nano-scale powder prepared by the method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: The invention comprises the nano-scale powder as claimed in claim 9.